2017
DOI: 10.1080/19315864.2017.1408725
|View full text |Cite
|
Sign up to set email alerts
|

They’re Doing What? A Brief Paper on Service Use and Attitudes in ASD Community-Based Agencies

Abstract: This brief paper examined the community services delivered to youth with autism spectrum disorder (ASD) in a Southern Californian city as a way to better understand ASD service provision and service attitudes. Specific goals of the study were to identify the services being delivered within the area, and how the use, perceived evidence and value attached to these services mapped onto recent systematic ASD service reviews. Forty-six providers completed the ASD Strategies and Interventions Survey (ASD-SIS), which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 25 publications
(34 reference statements)
1
10
0
Order By: Relevance
“…Results from this survey align with those of previous studies that interventions used when working with students with ASD are not always based on scientific evidence (Burns &Ysseldyke, 2009; Hess et al, 2008; Pickard et al, 2018). Although many educators participating in the study reported use of EBPs as the interventions used in their classrooms, many also reported use of interventions and supports with no evidence to support their use.…”
Section: Discussionsupporting
confidence: 85%
“…Results from this survey align with those of previous studies that interventions used when working with students with ASD are not always based on scientific evidence (Burns &Ysseldyke, 2009; Hess et al, 2008; Pickard et al, 2018). Although many educators participating in the study reported use of EBPs as the interventions used in their classrooms, many also reported use of interventions and supports with no evidence to support their use.…”
Section: Discussionsupporting
confidence: 85%
“…VS are one of the common, psychosocial interventions recommended across the lifespan, for autistic people (Denne, Hastings, & Hughes, 2018; National Institute for Health and Clinical Excellence (NICE), 2011(NICE), , 2012Pickard, Meza, Drahota, & Brikho, 2018;SIGN, 2016). They are either 'low-tech' -objects, photos, pictures, symbols, or written words -or 'high tech' -on electronic devices.…”
mentioning
confidence: 99%
“…This is important because approximately 1 in 68 US children are diagnosed with ASD, and the majority of these children are eligible for services from ASD community providers (Centers for Disease Control and Prevention, 2014). However, not all of the services being delivered by ASD community agencies are EBPs (Paynter & Keen, 2015; Pickard, Meza, Drahota, & Brikho, 2018), and EBPs that are adopted by ASD community agencies may not be successfully implemented and sustained (Perrault, McClelland, Austin, & Sieppert, 2011; Nakamura et al., 2011). AMI CAP members were interested in finding a way to facilitate EBP implementation in community-based organizations that provide services to children with an ASD (heretofore referred to as ASD-CBOs).…”
mentioning
confidence: 99%